Evaluative Language in Economic Reports of the Belt and Road Initiative: A Corpus-Based Analysis of Xinhua - Tang, Yuxin; Shen, Lingfeng; He, Hao (Journal of Linguistics and Communication Studies, 2025)
This study investigates the use of evaluative language in English-language economic reports on the Belt and Road Initiative (BRI) published by Xinhua News Agency between 2015 and 2024. Drawing on a 95,000-word corpus of 120 articles, the research applies Appraisal Theory to identify patterns in how state-sponsored discourse constructs China’s global economic identity. The analysis reveals a systematic deployment of positive appraisal across Judgment and Appreciation categories, often intensified through Graduation and supplemented by externally validated voices. These patterns strategically position China as a visionary, trustworthy development leader while framing partner countries as aligned and grateful participants. Evaluation, in this context, is not merely descriptive but functions as a rhetorical device for legitimizing China’s global role, projecting ideological coherence, and naturalizing asymmetrical development relations. The findings call for a critical reassessment of how linguistic repetition, lexical regularity, and discursive framing in state media contribute to the construction of geopolitical narratives in economic journalism.